Pengaruh Perencanaan Pajak, Aset Pajak Tangguhan dan Beban Pajak Tangguhan terhadap Manajemen Laba - Selly Eka Nur Cahni; Nur Rahmanti Ratih; Muhammad Alfa Niam (Akuntansi Pajak dan Kebijakan Ekonomi Digital, 2025)
This study focuses on examining the relationship between tax planning, deferred tax assets, and deferred tax liabilities on earnings management. The research method used is quantitative with a descriptive approach. The population of the study consists of manufacturing companies in the food and beverage subsector listed on the Indonesia Stock Exchange during the period 2022–2023. The sample comprises 47 company financial statements obtained through purposive sampling, with secondary data as the main source. Data analysis was conducted using multiple linear regression to determine the relationship between the variables under study: tax planning, deferred tax assets, deferred tax liabilities, and earnings management. The results indicate that tax planning and deferred tax liabilities significantly affect earnings management. This suggests that companies can use tax planning strategies to influence reported earnings and manage deferred tax liabilities to achieve desired managerial objectives, such as optimizing tax payments or adjusting earnings levels. However, deferred tax assets do not show a significant impact on earnings management, which may be due to other factors not observed in this study, such as internal company policies or different approaches to managing tax assets. Simultaneously, the findings confirm that all three variables have an impact on earnings management, contributing 10.3%. The remaining 89.7% of the impact comes from other factors not covered in the scope of this research, such as macroeconomic factors, government policies, or even the varying accounting practices of different companies. These findings provide valuable insights into how tax management influences earnings management and open opportunities for further research to better understand other variables that may affect corporate earnings management practices.